2013
DOI: 10.1177/000313481307901213
|View full text |Cite
|
Sign up to set email alerts
|

One-step Laparoscopic and Endoscopic Treatment of Gallbladder and Common Bile Duct Stones: Our Experience of the Last 9 Years in a Retrospective Study

Abstract: The optimal timing and best method for removal of common bile duct stones (CBDS) associated with gallbladder stones (GBS) is still controversial. The aim of this study is to investigate the outcomes of a single-step procedure combining laparoscopic cholecystectomy (LC), intra-operative cholangiography (IOC), and endoscopic retrograde cholangiopancreatography (ERCP). Between January 2003 and January 2012, 1972 patients underwent cholecystectomy at our hospital. Of those, 162 patients (8.2%; male/female 72/90) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…Studies have proven that this modified technique can effectively reduce the surgical time, as well as the endoscopic part of LC + ERCP/LERV, compared with the traditional technique [ 18 ]. In the management of cholelithiasis and concomitant choledocholithiasis, LERV reduces post-ERCP pancreatitis, reduces hospitalisation stay, and increases patient compliance [ 19 , 20 ]. However, from a logistical standpoint, it can be difficult to synchronise those two procedures [ 2 ].…”
mentioning
confidence: 99%
“…Studies have proven that this modified technique can effectively reduce the surgical time, as well as the endoscopic part of LC + ERCP/LERV, compared with the traditional technique [ 18 ]. In the management of cholelithiasis and concomitant choledocholithiasis, LERV reduces post-ERCP pancreatitis, reduces hospitalisation stay, and increases patient compliance [ 19 , 20 ]. However, from a logistical standpoint, it can be difficult to synchronise those two procedures [ 2 ].…”
mentioning
confidence: 99%
“…This statement was made with reference to the following information and papers [236][237][238][239][240][241][242][243].…”
Section: Bq3-(2)-3 What Are the Treatment Options For Cbds Associated...mentioning
confidence: 99%
“…Implementation of one-stage (OS) treatment tacticsendoscopic retrograde cholangiopancreatography, endoscopic papillosphincterotomy, choledocholitholithorectomy followed by laparoscopic cholecystectomy (ERCP + EPST + CLE + LCE) under one anesthesia can be one of the optimal methods for reducing the duration of choledochaemia and the frequency of recurrent inpatient treatment reducing costs for this category of patients. Several European studies have shown satisfactory results with one-stage ERCP + EPST + CLE + LCE compared with traditional two-stage (TS) treatment (ERCP + PEPT + CLE + LCE after 1-3 months) [5][6][7].…”
Section: Introductionmentioning
confidence: 99%